Deformations of circle-valued Morse functions on surfaces - Maksymenko, S.I. (Український математичний журнал, 2010)
Let M be a smooth connected orientable compact surface and let Fcov(M,S1) be a space of all Morse functions f : M → S₁ without critical points on ∂M such that, for any connected component V of ∂M, the restriction f : V → S₁ is either a constant map or a covering map. The space Fcov(M,S₁) is endowed with the C ∞-topology. We present the classification of connected components of the space Fcov(M,S₁). This result generalizes the results obtained by Matveev, Sharko, and the author for the case of Morse functions locally constant on ∂M.